Opting for the middle ground – blended sustainability as the way forward - Mockshell, Jonathan Yaw (DLG-Verlag GmbH, 2018)
In both developed and developing countries, policy stakeholders are tussling with the question of whether to promote agroecological intensification or sustainable agricultural intensification to deal with the multiple burden of a growing population, a changing climate, environmental degradation, and a precarious food and nutrition security situation. This has nurtured intense debates and created an impasse among policy actors. Blended sustainability could be a way out.